1999
DOI: 10.1002/(sici)1099-1050(199903)8:2<151::aid-hec411>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Internal markets and health care efficiency: a multiple-output stochastic frontier analysis

Abstract: This paper has two purposes. The first purpose is methodological and aims to extend previous work on efficiency analysis by implementing a multiple-output stochastic ray frontier production function model. This model generalizes the single-output stochastic frontier model to multiple-input, multiple-output technologies and allows simultaneous estimation of technical efficiency and analysis of influential variables on efficiency. The second, empirical, purpose is to test for existence and magnitude of the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 19 publications
2
49
0
1
Order By: Relevance
“…In a study (Gerdtham et al, 1999) covering the period 1989-1995, the trend in productivity was compared for hospitals operating under activity-based financing and hospitals operating under budget frame financing. The study showed that those hospitals operating under activity-based financing increased their productivity more than the hospitals in the control group.…”
Section: Studies That Indicate Productivity Increasesmentioning
confidence: 99%
“…In a study (Gerdtham et al, 1999) covering the period 1989-1995, the trend in productivity was compared for hospitals operating under activity-based financing and hospitals operating under budget frame financing. The study showed that those hospitals operating under activity-based financing increased their productivity more than the hospitals in the control group.…”
Section: Studies That Indicate Productivity Increasesmentioning
confidence: 99%
“…Table 1 shows the most commonly used inputs and outputs in previous DEA studies when comparing hospitals. Number of Outpatient visits (Bwana 2015 ;Flokou et al, 2011;Masiye et al, 2006 ;Ramanathan 2005;Zuckerman et al, 1994) Number of beds (Bwana 2015;Kose et al, 2014, Al-Shammari 1999Akazili et al, 2008;Harrison et al, 2004;Puig-Junoy 2000;Weng et al, 2009;Magnussen 1996) Number of Inpatient visits (Chuang et al, 2011;Butler and Li 2005;Tsai and Molinero 2002;Zere et al, 2001;Banker et al, 1986 ;Kawaguchi et al, 2014) Number of doctors (Grosskopf and Valdmanis 1987;Kirigia et al, 2008;Chang et al, 2004;Huang et al, 1989;Prior 2006;Kose et al, 2014;Dotoli et al, 2015) Number of major and minor surgeries (Al-Shammari 1999;Chang et al, 2004 ;Puig-Junoy 2000 ;Gerdtham et al, 1999 ;Dotoli et al, 2015) Number of nurses (Chuang et al, 2011;Masiye et al, 2006;Hollingsworth and Parkin 1997;Byrnes and Valdmanis 1993;Kawaguchi et al, 2014) Number of emergency visits (Butler andLi 2005 Grosskopf andValdmanis 1987;<...>…”
Section: Selection Of Input and Output Variables In The Dea Modelmentioning
confidence: 99%
“…Previous studies of hospital inefficiency have also examined the effects of external changes in market and regulatory environments such as the implementation of the prospective payment system (PPS) in 1983 [26,32], the growth and penetration of managed care [30,33], and government budget and health care reforms [34,35]. In response to the growing concern over health care quality in the late 1990s and early 2000s, many researchers have also focused on the effects of financial pressure placed on hospitals as a result of PPS payments and penetration of HMOs in local hospital markets on both the level of technical efficiency and quality of care in hospitals [35,36].…”
Section: Literature Reviewmentioning
confidence: 99%